Solving the puzzle of Parkinson's disease using induced pluripotent stem cells. (November 2014) - Zhao, Ping; Luo, Zhiwei; Tian, Weihua; Yang, Jiayin; Ibáñez, David P; Huang, Zhijian; Tortorella, Micky D; Esteban, Miguel A; Fan, Wenxia
The prevalence and incidence of Parkinson's disease (PD) is increasing due to a prolonged life expectancy. This highlights the need for a better mechanistic understanding and new therapeutic approaches. However, traditional in vitro and in vivo experimental models to study PD are suboptimal, thus hampering the progress in the field. The epigenetic reprogramming of somatic cells to induced pluripotent stem cells (iPSCs) offers a unique way to overcome this problem, as these cells share many properties of embryonic stem cells (ESCs) including the potential to be transformed into different lineages. PD modeling with iPSCs is nowadays facilitated by the growing availability of high-efficiency neural-specific differentiation protocols and the possibility to correct or induce mutations as well as creating marker cell lines using designer nucleases. These technologies, together with steady advances in human genetics, will likely introduce profound changes in the way we interpret PD and develop new treatments. Here, we summarize the different PD iPSCs reported so far and discuss the challenges for disease modeling using these cell lines.